Five‐year cumulative incidence of overweight and obesity, and longitudinal change in body mass index in Japanese workers: The Japan Epidemiology Collaboration on Occupational Health Study - Hasegawa, Miyuki (J Occup Health, 2019)
OBJECTIVE: The present study aimed to estimate cumulative incidence of overweight and obesity and describe 5‐year longitudinal changes in body mass index (BMI) in a large occupational cohort in Japan. METHODS: Participants were 55 229 Japanese employees, who were aged 20‐59 years and attended at all subsequent annual health check‐ups between 2009 and 2014. Mixed model analysis was performed to examine the effects of age and cohort by gender on BMI change, with age as a random variable. Cumulative incidence of overweight (23.0≤ BMI <27.5 kg/m(2)) and obesity (BMI ≥27.5 kg/m(2)) was calculated. Logistic regression analysis was used to estimate odds ratios for the incidence of overweight and obesity according to age group. RESULTS: The incidence of overweight and obesity was approximately double in men (28.3% and 6.7%, respectively) compared to women (14.3% and 3.9%, respectively).The incidence of obesity decreased with age in men, but did not differ according to age in women (P for trend: .02 and .89, respectively). Among overweight participants, the incidence of obesity was higher in women (18.9%) than men (14.5%) and decreased with advancing age (P for trend: <.001 in men and .003 in women). Mean BMI was higher in men than women in all age groups throughout the period. Younger cohorts tended to have a higher BMI change compared with older cohorts. CONCLUSIONS: In this Japanese occupational cohort, transition from overweight to obesity is higher in women than men, and the more recent cohorts had a higher change in mean BMI than the older cohorts.